(untitled) (African Journal of Biomedical Research, 2021)
This study evaluated the knowledge, attitude, and uptake of the Hepatitis B vaccine among walk-in customers in two community pharmacies in Ibadan, Nigeria. A cross-sectional study was conducted among the study participants. Data was summarized with descriptive and inferential analysis, with significance level set at p < 0.005. A total of 764 walk-in customers: 395 (51.7%) at Maxi Pharmacy and 369 (48.3%) at Vanguard Pharmacy, were recruited for the study. Mean scores for HBV infection knowledge and attitude were 6.29 ± 2.81 (out of a maximum obtainable score of 12) and 5.76 ± 2.10 (out of a maximum obtainable score of 10), respectively. Only 82 (10.7%) participants had been vaccinated against HBV infection. Bivariate analysis showed that gender, awareness, vaccination, and level of formal education were predictors of HBV knowledge and attitude. Age only predicted HBV knowledge significantly, but not attitude. Five hundred and sixty-five (74.0%) participants were aware of HBV. Ninety-two (12.0%) participants reported that a member of their immediate family was vaccinated against HBV while 82 (10.7%) participants had been vaccinated against HBV. Out of the 168 participants who reported how they became aware of Hepatitis B, 31 (18.5%) was through social media, 32 (19.0%) internet, 8 (4.8%) textbook, 22 (13.1%) school, 35 (20.8%) family/friends, 41 (24.4%) hospital/pharmacy, and 4 (2.4%) through infected people. The study revealed average levels of HBV knowledge and vaccination among study participants, despite high levels of awareness and positive attitude to HBV.